2019
DOI: 10.3390/jpm9010005
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Checkpoint Inhibition in Microsatellite Stable Colorectal Cancer

Abstract: Checkpoint inhibitor therapy has introduced a revolution in contemporary anticancer therapy. It has led to dramatic improvements in patient outcomes and has spawned tremendous research into novel immunomodulatory agents and combination therapy that has changed the trajectory of cancer care. However, clinical benefit in patients with colorectal cancer has been generally limited to tumors with loss of mismatch repair function and those with specific germline mutations in the DNA polymerase gene. Unfortunately, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Recent preclinical and clinical studies have shown that ICIs combined with chemotherapy, molecular targeted therapy, radiotherapy, or new immunomodulators can act synergistically and extend the application of ICIs to MSS type CRC. 7,110,111…”
Section: Crosatellite S Tatus and Appli C Ati On Prog Re Ss Of I Cismentioning
confidence: 99%
“…Recent preclinical and clinical studies have shown that ICIs combined with chemotherapy, molecular targeted therapy, radiotherapy, or new immunomodulators can act synergistically and extend the application of ICIs to MSS type CRC. 7,110,111…”
Section: Crosatellite S Tatus and Appli C Ati On Prog Re Ss Of I Cismentioning
confidence: 99%
“…Although improved responses with immunotherapy have been reported in patients with metastatic MSI-H/dMMR CRCs, these responses are not seen in the majority of MSS/pMMR CRCs. Numerous trials of combined immunotherapy with other agents aimed at "sensitizing" these tumors are ongoing [132,133].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…The immunological benefit in patients with colorectal cancer has been limited to those who had a loss of mismatch repair function and had specific germline mutations in the DNA polymerase gene[34,35]. A host of current trials are underway in patients with microsatellite stable (MSS) CRC to evaluate the utility of concurrent chemotherapy, VEGF/EGFR inhibitors, radiotherapy, or MEK inhibitors with ICIs; however, more data are still needed to address the efficacy and tolerability of ICIs in MSS CRC patients[36].…”
Section: Immunotherapy and Gi Tumorsmentioning
confidence: 99%